1993
DOI: 10.1111/j.1550-7408.1993.tb04902.x
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Pneumocystis carinii Culture1

Abstract: Published and unpublished data on the cultivation of P. carinii were reviewed by a panel of investigators convened by the National Institutes of Health. Although several cell culture systems allow propagation of P. carinii for a limited time with modest rates of replication, these have not proved adequate for isolation of P. carinii in sufficient quantity to explore important basic biological investigation. Attempts at cell-free culture have yielded only transient proliferation. Because much of the unsuccessfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 19 publications
2
52
0
Order By: Relevance
“…Other limitations of these studies include the possibility that the observed response of human AMs to rodent-derived Pneumocystis may reflect in part the origin of the organisms. Unfortunately, in the absence of reliable culturing methods, Pneumocystis of human origin are not available (Sloand et al, 1993). However, the recent observation that rat-derived Pneumocystis elicit similar chemokine and NF-B responses comparing human AMs to rat AMs in part validates the use of this model (Zhang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Other limitations of these studies include the possibility that the observed response of human AMs to rodent-derived Pneumocystis may reflect in part the origin of the organisms. Unfortunately, in the absence of reliable culturing methods, Pneumocystis of human origin are not available (Sloand et al, 1993). However, the recent observation that rat-derived Pneumocystis elicit similar chemokine and NF-B responses comparing human AMs to rat AMs in part validates the use of this model (Zhang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Since the organism cannot be readily grown in vitro, the traditional quantification method for P. carinii is enumeration of organisms by microscopic examination, which is difficult and cumbersome due to the organism's growth in clusters and the presence of different morphological forms (14,19). Different stains vary in their sensitivities of detection as well as in their abilities to detect the different forms of P. carinii.…”
mentioning
confidence: 99%
“…carinii, the common subspecies infecting the immunosuppressed laboratory rat, which is the most commonly used in vivo model of PCP (2,19). We then assessed this new assay during studies attempting to establish the continuous axenic culture system recently described by Merali et al (14).…”
mentioning
confidence: 99%
“…Recently, P. carinii has been detected by PCR DNA amplification of blood from rats and human patients with PCP and with disseminated pneumocystosis, thus helping to answer a number of important questions about the pathogenesis of P. carinii infection.2i , Considering the potential importance of detection of the organism in the blood, a culture method was used which has been employed extensively for the short-term culture of rat-or human-derived P. carinii. 17, 18 In the current study, the cell line was infected with a different inoculum source, which consisted of PBMC from human patients with P. carinii infection instead of conventional inocula.…”
Section: Discussionmentioning
confidence: 99%